Long-term evaluation of the central vault after phakic Collamer® lens (ICL) implantation using OCT - Alfonso, José F. (2012)
PURPOSE: The aim of this work is to evaluate the changes in the central vault after using implantable Collamer® lenses (ICL) to correct myopia. METHODS: This cohort study included 133 eyes; mean spherical equivalent -9.47 ± 3.71 diopters (D) (range: -2.75 to -22.25 D) who underwent ICL V4 implantation. Besides a complete ophthalmologic examination, the central vaulting was measured with Visante OCT and evaluated between different periods of follow-up (1 week, 1, 3, and 6 months, and yearly postoperatively). Post-operative time ranged from 6 to 73 months. RESULTS: Within the first 6 months, the mean central vaulting dropped from 510 ± 238 μm (range 100 to 940 μm) to 439 ± 231 μm (range 90 to 910) a significant decrease by 71 ± 58 μm (range -170 to 30 μm) (p = 0.028) with a trend to a lower reduction after this period. After 36 month from ICL implantation, this variation tends to be smaller with the majority of the eyes having a mean decrease smaller than 2 μm per month. Initial vault (Spearman Rho = -0.237, p = 0.006) was the factor more significantly associated with decrease in vault; eyes presenting a reduction in vault >100 μm had an average initial vault that was 141 μm and 184 μm higher than eyes with no change or with increase in vault over time, respectively. CONCLUSIONS: This study shows a continuous reduction of central vault over time. The reduction is highest during the first 6 months and tends to be lower and slow down over time. The decrease of vaulting was more pronounced in eyes with larger initial vaulting.